FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SEKOLAH DASAR DI SD NEGERI 101846 KECAMATAN KUTALIMBARU TAHUN 2025 - Susanti Br Perangin-angin; Putri Febriani; Teddy Bambang; Mustar Rusli; Erba Kalto (Poltekkes Kemenkes Medan, 2026)
Clean and Healthy Living Behavior (PHBS) is an important preventative measure for improving the health status of school-aged children. However, the implementation of PHBS in schools still faces various obstacles such as low student knowledge, unsupportive attitudes, and limited sanitation facilities. This can impact the health quality of students and reduce the effectiveness of school health programs. This study was conducted to analyze the factors related to PHBS actions among students at SD Negeri 101846 in Kutalimbaru Sub-district, Deli Serdang Regency, in 2025. This research used an analytical survey design with a cross-sectional approach, involving all 48 students in grades IV and V through a total sampling method. Data were collected using a structured questionnaire that covered variables such as knowledge, attitudes, availability of facilities, and PHBS actions. Data analysis was performed with the Chi- Square test using a significance level of 0.05. The study results showed that most students had low knowledge (58.3%), poor attitudes (56.3%), and rated the school's facilities as low (89.6%). Despite this, students' PHBS actions were relatively balanced, with 50% being good and 50% being poor. Statistical tests showed a significant relationship between knowledge and CHLB actions (p=0.000) and between attitudes and PHBS actions (p=0.004). However, the availability of facilities was not significantly related to actions (p=0.345). In conclusion, knowledge and attitude factors are more dominant in influencing student behavior than are facilities. Therefore, it is recommended that the school strengthen health education interventions, promote healthy habits, and enhance the role of teachers and parents in instilling PHBS from an early age.